School heads initiatives and teachers instructional practices in the new educational setting - Dilna, Armia K. (Edelweiss Applied Science and Technology, 2025)
Creating an educational environment that promotes effective learning and teaching remains a key responsibility of school heads. They actively engage in training and supporting teachers, which is crucial for enhancing instructional practices. This study investigates the relationship between school heads’ initiatives and teachers’ instructional practices within the new educational setting, focusing on three main areas: school environment, learning supports, and instructional practices. Using a descriptive correlation design, the research employed a self-made questionnaire tailored to the context of Datu Odin Sinsuat (DOS) school district in the Maguindanao-2 division of the Ministry of Basic, Higher, and Technical Education (MBHTE) in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). The study identified seventy-five (75) elementary teachers as respondents through complete total enumeration. The findings reveal that teachers who receive support from school heads are more likely to implement effective instructional practices in their classrooms. Furthermore, initiatives from school heads significantly enhance student learning outcomes by improving the school environment and providing necessary learning support. School heads can foster collaboration with teachers to identify areas for improvement, thereby creating an environment conducive to effective teaching practices. Generally, the school heads’ initiatives and teachers’ instructional practices in the new educational setting emphasize the importance of resource management, targeted professional development, and strong leadership in fostering a learning environment that promotes high student achievement. These components play a crucial role in ensuring all students receive a high-quality education and adapting to the evolving educational landscape.